1988
DOI: 10.1128/aem.54.9.2281-2286.1988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Species and Environmental Conditions on Ice Nucleation Activity of Pseudomonas syringae on Leaves

Abstract: Selected plant species and environmental conditions were investigated for their influences on expression of ice nucleation activity by 15 Pseudomonas syringae strains grown on plants in constant-temperature growth chamber studies. Ice nucleation frequencies (INFs), the fraction of cells that expressed ice nucleation at-5 or-9°C, of individual strains varied greatly, both on plants and in culture. This suggests that the probability of frost injury, which is proportional to the number of ice nuclei on leaf surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Plasmid pSFL12 was mutagenized with Tn3-HoHol by using previously described methods (51). Following matings with E. coli donors harboring pSFL12::Tn3-HoHol, colonies of P. syningae 31R1 that harbored fusion plasmids were selected on medium 925 (20) containing myo-inositol (10 g/liter) as a sole carbon source, tetracycline, ampicillin, and 5-bromo-4-chloro-3-indoyl-p-D-galactopyranoside (X-Gal) (40 ,ug/ml). After 3 days of incubation at 27°C, the colonies were screened for a blue color, which indicated that there was a Tn3-HoHol insertion downstream of a promoter.…”
Section: Materuils and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmid pSFL12 was mutagenized with Tn3-HoHol by using previously described methods (51). Following matings with E. coli donors harboring pSFL12::Tn3-HoHol, colonies of P. syningae 31R1 that harbored fusion plasmids were selected on medium 925 (20) containing myo-inositol (10 g/liter) as a sole carbon source, tetracycline, ampicillin, and 5-bromo-4-chloro-3-indoyl-p-D-galactopyranoside (X-Gal) (40 ,ug/ml). After 3 days of incubation at 27°C, the colonies were screened for a blue color, which indicated that there was a Tn3-HoHol insertion downstream of a promoter.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Individual leaflets from trifoliate leaves or individual root systems were placed in a washing buffer (40) and sonicated for 5 min to remove bacterial cells from tissue surfaces or rhizosphere soil. The washing buffer containing suspended bacterial cells was diluted, and bacterial population size was determined by spreading aliquots of dilutions on King's medium B (17) containing rifampin, using previously described methods (33,40). The ice nucleation activities of bacteria inhabiting the rhizosphere or phyllosphere were determined by the dropletfreezing assay (24).…”
Section: Materuils and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the large aggregates are labile, a variable and typically small fraction of all cells will possess activity at these warm temperatures. For example, O'Brien and Lindow [1988] observed the fraction of INA P. syringae strains grown on plants able to nucleate at −5°C to range from 1 in 30 to 1 in 20,000 for a variety of experimental conditions. At colder temperatures clusters of a few proteins are enough to trigger freezing, so that by −10°C to −12°C the nucleation frequency may be 1 in 10 cells or higher [ Hirano and Upper , 2000; Kim et al , 1987]; a single Ina protein nucleates at −12 to −13°C [ Govindarajan and Lindow , 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the gene responsible for this property is present in the genome, bacterial ice nucleation is not always fully expressed. Nutritional and environmental factors influence this expression and the subsequent ice nucleation activity of the bacterium (O'Brien et al, 1988;Nemecek-Marshall et al, 1993). It is not known if such variability exists in other organisms with ice nucleation activity.…”
Section: Introductionmentioning
confidence: 99%